Cognitive training in Parkinson disease: Cognition-specific vs nonspecific computer training. - Zimmermann, Ronan; Gschwandtner, Ute; Benz, Nina; Hatz, Florian; Schindler, Christian; Taub, Ethan; Fuhr, Peter (Neurology, 2014)
OBJECTIVE: In this study, we compared a cognition-specific computer-based cognitive training program with a motion-controlled computer sports game that is not cognition-specific for their ability to enhance cognitive performance in various cognitive domains in patients with Parkinson disease (PD). METHODS: Patients with PD were trained with either a computer program designed to enhance cognition (CogniPlus, 19 patients) or a computer sports game with motion-capturing controllers (Nintendo Wii, 20 patients). The effect of training in 5 cognitive domains was measured by neuropsychological testing at baseline and after training. Group differences over all variables were assessed with multivariate analysis of variance, and group differences in single variables were assessed with 95% confidence intervals of mean difference. The groups were similar regarding age, sex, and educational level. RESULTS: Patients with PD who were trained with Wii for 4 weeks performed better in attention (95% confidence interval: -1.49 to -0.11) than patients trained with CogniPlus. CONCLUSIONS: In our study, patients with PD derived at least the same degree of cognitive benefit from non-cognition-specific training involving movement as from cognition-specific computerized training. For patients with PD, game consoles may be a less expensive and more entertaining alternative to computer programs specifically designed for cognitive training. CLASSIFICATION OF EVIDENCE: This study provides Class III evidence that, in patients with PD, cognition-specific computer-based training is not superior to a motion-controlled computer game in improving cognitive performance.